Error awareness and the error-related negativity: evaluating the first decade of evidence - Wessel, Jan R. (Frontiers in Human Neuroscience, 2012)
From its discovery in the early 1990s until this day, the error-related negativity (ERN) remains the most widely investigated electrophysiological index of cortical error processing. When researchers began addressing the electrophysiology of subjective error awareness more than a decade ago, the role of the ERN, alongside the late error positivity (Pe), was an obvious locus of attention. However, the first two studies explicitly addressing the role of error-related ERPs would already set the tone for what still remains a controversy today: An initial study reported significant differences in ERN amplitude with respect to subjective error awareness, whereas the second failed to report this result, leading to a myriad of follow-up studies that seemed to back up or contradict either view. Here, I review those studies that explicitly dealt with the role of the error-related ERPs in subjective error awareness, and try to explain the differences in reported effects. From the point of view presented here, the different findings between studies can be explained by disparities in experimental design and data analysis, specifically with respect to the quantification of subjective error awareness. Based on the review of these results, I will then try to embed the error-related negativity into a widely known model of the implementation of access consciousness in the brain, the global neuronal workspace model, and speculate as the ERN’s potential role in such a framework. At last, I will outline future challenges in the investigation of the cortical electrophysiology of error awareness, and offer some suggestions on how they could potentially be addressed.